Transplanting organs from hepatitis B positive donors: Is it safe? Is it ethical?. Issue 10 (14th August 2018) - Anwar, Nadeem; Sherman, Kenneth E.
Summary: Liver transplant centres throughout the USA face a huge shortage of liver organs for their wait‐listed patients. Various types of innovations are being considered for expansion of this donor pool. Organs that were previously deemed to be high risk are now being considered for transplantation. For the last 25 years, hepatitis B core antibody (anti‐HBc+) organs have been used for liver transplantation. While the initial transplantations did reveal a high incidence of de novo hepatitis (DNH) in the recipients, the medical knowledge and experience have evolved and this risk has been markedly decreased. In this paper, medical literature evaluating the safety of such organ transplants has been reviewed. There is strong evidence to suggest that using anti‐HBc+ organs with appropriate prophylaxis after transplant is a safe practice with good patient and graft survivals. In the second half of the paper, we discuss whether it is ethical to use anti‐HBc+ organs. We argue that the use of such organs is in compliance with the principles of medical ethics and that society at large benefits from the use of these organs. Hence, we recommend that the use of such organs is both safe and ethical and this practice should be continued in the future.